Aplikasi Pembelajaran Tatacara Shalat Jumat Berbasis Android - Ferry Dwi Setiyawan; R. Rizal Isnanto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2015)
For male muslim eid on Friday is obligatory. But in practice there are problems such as application of procedures for Friday prayers is not appropriate and make the pilgrims do not pray with good. For that reason, need a method of learning and innovation easier and more attractive to use technology in the field of islamic learning especially for procedures Friday prayers. As many smartphone users with an operating system android, then made learning application procedures for Friday prayers based on android. The application of learning is made using software Eclipse IDE and Android SDK with Java as a programming language. Stages of development software used is SDLC (Software Development Life Cycle) by using the method waterfall, as modeling software used is UML (Unified Modelling Language). Steps in this research is software requirement analysis, design, coding, testing and maintenance. Functional testing using a method of black box. The result of this research is application procedures of friday prayers learning based on Android can be use to learning friday prayers. The application can run well on a device with a minimum of android operating system version sandwitch 4.0 (Ice Cream Sandwitch) with the storage space available mb of 7MB. Function menus and buttons is going according to their respective functions. This application for procedures of friday prayers can be used as a medium for learning friday prayers.